Microenvironment improvement protocol for the sensitive spectrofluorimetric determination of an hepatitis C virus antiviral (Simeprevir): application to human plasma. (17th December 2019) - Derayea, Sayed M.; A. El Hamd, Mohamed; Ali, Sayed; Samir, Ebtihal
Abstract: Simeprevir (SPV) is a powerful antihepatitis C virus agent that was newly introduced into the pharmaceutical market. We here established and validated an easy, simple, and sensitive spectrofluorimetric method for its estimation at λem 427 nm (λex 337 nm). The suggested procedure was based on two times enhancement in the original emission of SPV through modifying its microenvironment in buffered aqueous solution by adding Triton X‐100. The relationship between the concentration of SPV and the observed fluorescence intensity was linear in the range 0.06–1.0 μg ml −1 with a correlation coefficient of 0.9997. The limits of detection and quantitation were 21 and 64 ng ml −1, respectively. The present method was effectively applied to quantify SPV content in pharmaceutical tablets and human plasma spiked with the drug with no interference from tablet excipients or plasma components.